A comparative study of the place of self-sacrifice in moral education from the point of view of Islam and Judaism - hassan farzi; Seyyed Akbar Hosseini; Mahmud Namazi (اخلاق وحیانی)
Moral education, in the sense of the process of institutionalizing moral values in human existence, is considered one of the most important missions of divine religions. The general structure of these values is the same in different religions, but the moral teachings that are the practical manifestation of these values are different in some details. What is the place of "sacrifice" as an important moral doctrine in moral education? This article examines the place of this doctrine in moral education based on the teachings of Islamic and Jewish sharia by referring to library sources and using the descriptive-analytical method. Both Shari'ahs propose selflessness and sacrifice towards others as one of their most important educational teachings, but they differ in determining its criteria - as a moral act. Paying attention to the race of people in determining examples of self-sacrifice is the most important criterion that exists in Judaism - in its present form; In the sense that self-sacrifice against a non-Jew can have a negative value. On the other hand, the only criterion for self-sacrifice towards others in Islam is that it should be based on God's service. Paying attention to this axis in practice means that only the enemies of God and people who suffer from moral diseases such as wonder and arrogance are not included in the scope of self-sacrifice.